Sarcoma Metastatic to the Right Ventricle: Surgical Intervention Followed by Prolonged Survival - Harting, Matthew T. (2004)
Malignant tumors that metastasize to the heart pose a formidable therapeutic challenge. Recent advances in surgical treatment have improved the management and prognosis of patients with cardiac metastases. We report the case of a 45-year-old man who had a high-grade pleomorphic sarcoma of the right ventricle. We completely resected the neoplasm, reconstructed the right ventricle, and replaced the mitral valve. Upon late follow-up, 67 months (5.6 years) later, the patient was alive and well. This case shows that aggressive surgical management of malignant disease metastatic to the heart can enable prolonged survival.